Coupling of Reformatsky Reagents with Aryl Chlorides Enabled by Ylide‐Functionalized Phosphine Ligands. Issue 12 (28th January 2021) - Hu, Zhiyong; Wei, Xiao‐Jing; Handelmann, Jens; Seitz, Ann‐Katrin; Rodstein, Ilja; Gessner, Viktoria H.; Gooßen, Lukas J.
Abstract: The coupling of aryl chlorides with Reformatsky reagents is a desirable strategy for the construction of α‐aryl esters but has so far been substantially limited in the substrate scope due to many challenges posed by various possible side reactions. This limitation has now been overcome by the tailoring of ylide‐functionalized phosphines to fit the requirements of Negishi couplings. Record‐setting activities were achieved in palladium‐catalyzed arylations of organozinc reagents with aryl electrophiles using a cyclohexyl‐YPhos ligand bearing an ortho‐tolyl‐substituent in the backbone. This highly electron‐rich, bulky ligand enables the use of aryl chlorides in room temperature couplings of Reformatsky reagents. The reaction scope covers diversely functionalized arylacetic and arylpropionic acid derivatives. Aryl bromides and chlorides can be converted selectively over triflate electrophiles, which permits consecutive coupling strategies. Abstract : Ylide‐functionalized phosphines were tailored to fit the requirements of room‐temperature Negishi couplings of aryl chlorides. YPhos/Pd catalyst is highly efficient for the coupling with aryl chlorides in general, and the reaction shows excellent functional group compatibility. This allows the selective coupling of aryl electrophiles in the competitive reaction as demonstrated in the synthesis of ibuprofen.